High Performance Digital Circuit Techniques - Sadrossadat, Sayed Alireza (University of Waterloo, 2009)
Achieving high performance is one of the most difficult challenges in designing digital circuits. Flip-flops and adders are key blocks in most digital systems and must therefore be designed to yield highest performance. In this thesis, a new high performance serial adder is developed while power consumption is attained. Also, a statistical framework for the design of flip-flops is introduced that ensures that such sequential circuits meet timing yield under performance criteria. Firstly, a high performance serial adder is developed. The new adder is based on the idea of having a constant delay for the addition of two operands. While conventional adders exhibit logarithmic delay, the proposed adder works at a constant delay order. In addition, the new adder's hardware complexity is in a linear order with the word length, which consequently exhibits less area and power consumption as compared to conventional high performance adders. The thesis demonstrates the underlying algorithm used for the new adder and followed by simulation results. Secondly, this thesis presents a statistical framework for the design of flip-flops under process variations in order to maximize their timing yield. In nanometer CMOS technologies, process variations significantly impact the timing performance of sequential circuits which may eventually cause their malfunction. Therefore, developing a framework for designing such circuits is inevitable. Our framework generates the values of the nominal design parameters; i.e., the size of gates and transmission gates of flip-flop such that maximum timing yield is achieved for flip-flops. While previous works focused on improving the yield of flip-flops, less research was done to improve the timing yield in the presence of process variations.
Keywords: Yield maximization; Process variation; Statistical design; Electrical and Computer Engineering